Pengembangan Kemampuan Manusia Dalam Sudut Pandang Pendidikan Islam - Bias Tirta Bayu; Sri Mei Ulfani; Ratih Kumala Sari; Ibnu Majah; Wismanto Wismanto (Pusat Riset dan Inovasi Nasional, 2024)
Humans as God's special creation indeed have a life background that is full of secrets. Humans are God's most potential creatures. Education is very important in human life and cannot be separated from all aspects. The aim of this research is to determine the development of human potential from an Islamic education perspective. This research uses a qualitative descriptive method, the type of research is library research, namely research through library or literature review. The data source in this research is primary data, namely books that directly discuss the problem being studied, namely theoretical studies or literature reviews on the Development of Human Potential in the Perspective of Islamic Education. The results of the discussion of this research are that the term education in the Islamic context generally refers to the Koran and Hadith. There are three terms, namely al-tarbiyah, al-ta'dib and al-ta'lim. Islamic education in general is a systematic effort to help students grow and develop through self-actualization of potential based on the moral principles of the Koran and Hadith. There are several objectives, basics, principles and values ​​of Islamic education